Evaluation of serum alkaline phosphatase and serum creatinine level in chronic periodontitis patients before and after non-surgical periodontal therapy - Jinjala, Aarti L.; Brahmbhatt, Nilam A; Dulani, Kirti S.; Pandya, Mit (International Journal Of Community Medicine And Public Health, 2025)
Background: This study aimed to quantitatively evaluate and compare serum alkaline phosphatase (ALP) and serum creatinine (SCr) levels in chronic periodontitis patients before and after non-surgical periodontal therapy (NSPT), and compare these levels with periodontally healthy individuals. Methods: Eighty participants, aged 30-50 years, were recruited: 40 with chronic generalized periodontitis (study group) and 40 periodontally healthy individuals (control group). Clinical parameters including simplified oral hygiene index (OHI-S), gingival index (GI), probing depth (PD), and clinical attachment level (CAL) were measured at baseline for both groups. Blood samples were collected from both groups at baseline for ALP and SCr estimation. The both groups received phase I therapy. On day 30 post-NSPT, clinical parameters and blood samples were re-evaluated for the study group. The results were statistically analysed using paired t test and one way ANOVA. Results: At baseline, the chronic periodontitis group exhibited significantly higher serum ALP levels compared to the healthy control group. Following NSPT, a significant decrease in serum ALP levels (<0.001) was observed in the chronic periodontitis group, accompanied by significant improvements clinical parameters. SCr levels were found to be significantly higher in the periodontitis group at baseline compared to healthy controls. However, no statistically significant (≈0.53) change was observed in SCr levels in the periodontitis group following NSPT. Conclusions: These results indicate that serum ALP may serve as a responsive biomarker of disease activity and therapeutic response in chronic periodontitis, while SCr though elevated at baseline does not respond to short term NSPT.